High C–C cleavage efficiencies of ethanol oxidation reaction on mesoporous RhPt electrocatalysts. Issue 6 (31st October 2022) - Yang, Sufang; Yang, Xiaobo; Cui, Xueqin; Gao, Xinhua; Zou, Houbing; Tong, Xili; Yang, Nianjun
Abstract: Optimizing the structure of an electrocatalyst is critical to achieve its outstanding performance as well as to establish relationships between its composition and its performance. In this work, a series of mesoporous RhPt electrocatalysts (RhPt‐MPS) with different compositions are designed and synthesized toward the ethanol oxidation reaction (EOR). The mesoporous structure of RhPt‐MPS exposes abundant surface sites and channels for mass transfer of ethanol, and thus boosts the catalytic EOR performance. It has been confirmed that Rh not only reduces the oxidation potential of EOR, but also effectively facilitates the breakage of C─C bond. Stemming from structural and compositional advantages of the RhPt0.6 ‐MPS electrocatalyst, it exhibits the highest activity (2846.0 mA mg –1 ) for the EOR when compared with other RhPt‐MPS, Rh‐MPS, and Pt‐MPS electrocatalysts. It also delivers excellent stability and high selectivity than other electrocatalysts. Abstract :